Gamification: Using Kahoot! to Make Students Love the Class from the Very Beginning - Ni Putu Ade Resmayani; Ida Nyoman Tri Darma Putra (Muhammadiyah University of Mataram, 2019)
The underlying purpose of this research was to discuss how to use Kahoot! as a new alternative to deliver the first meeting of an English class at the higher education level. One hundred twenty-five freshmen of Mataram Tourism Institute were experiencing, observed, and asked about the use of Kahoot! as teaching media to deliver the introduction of their course at the beginning of the class. There are twenty questions involved in this activity. Kahoot! got a positive response from the students while it appears no problem in meeting all of the first-class introduction objectives. Despite some lack of points of this gamification, more significant interaction between students, more attention to the course issues, and more motivation were observed. It is a highly recommended activity to apply in the first class meeting as an alternative to explain the course for the first time.